Do storage of Eugenia stipitata seeds affect their germination and efficacy of the tetrazolium viability test? (Bioagro, 2024)
Eugenia stipitata is a fruit species from the Amazon that is important in traditional medicine due to its therapeutic properties. Estimates of seed viability in this species are still scarce, and it is necessary to develop rapid tests to determine the quality of the seeds. The aim of this study was to determine the applicability of the tetrazolium test to estimate viability and germination in seeds of E. stipitata with and without storage. The design was completely randomised in a 2 x 2 factorial scheme with 10 replications. The results of the tetrazolium and germination tests show that seeds of E. stipitata lose their viability when stored for six months in water at ambient temperature. Neither small nor large seeds stored for six months in water at ambient temperature are recommended for use with the tetrazolium test. Small, freshly harvested, unstored seeds show a germination potential of 100%. The tetrazolium test is efficient in determining the viability of small and large seeds of Eugenia stipitate with no storage.
Keywords: Araçá-boi; calidad de la semilla; especies medicinales; viabilidad